Investigation of the Mechanical Properties of Bagasse Fiber-Reinforced Epoxy Composite using Taguchi and Response Surface Methodology - Karuppusamy Kanthavel; Ramanaicker Palanisamy; Somasundaram Vivek (BioResources, 2015)
Fiber-reinforced polymer composites are widely used in various applications because of their mechanical properties and ease of manufacture. Fiber-reinforced plastics are being developed using synthetic fiber and natural fibers of bagasse, palm biomass, etc. In this study, the mechanical strength of bagasse fiber-reinforced epoxy composite was investigated using a Design of Experiment technique. The parameters of fiber volume percentage, alkali concentration, and treatment time with three levels were considered, and an L27 design matrix was developed using the Taguchi orthogonal array. The bagasse was first treated with sodium hydroxide solution (NaOH); subsequently, 27 specimens were developed for experimental investigation. The mechanical strength of newly developed bagasse fiber-reinforced epoxy composite was investigated using a three-point bending testing machine. The flexural strength was calculated using three-point bending strength for length versus load combination. The analysis and optimization was done using the Taguchi method, and a second-order mathematical model was developed using response surface methodology (RSM). A significant performance improvement in the flexural strength of the newly developed composite was found.